2022
DOI: 10.3390/cancers14143490
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine–Curcumin Complex-Loaded Amine-Functionalised Hollow Mesoporous Silica Nanoparticles for Breast Cancer Therapy

Abstract: The current study focuses on developing a tumour-targeted functionalised nanocarrier that wraps hollow mesoporous silica nanoparticles. The guanidine carbonate and curcumin are immobilised on the surface of 3-aminopropyl-triethoxy silane (APTES)-decorated hollow mesoporous silica nanoparticles (HMSNP), as confirmed through XPS and NMR analysis. XPS analysis demonstrates that the shape of the hysteresis loops is modified and that pore volume and pore diameter are consequently decreased compared to control. Guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The CCC bond angle was theoretically reported as 113.79° and experimentally as 112.8°. These reported parameters have been similar to the optimized structure of gemcitabine and docetaxel complex, that confirms that the structural features of GEDT were in the reported range [43].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The CCC bond angle was theoretically reported as 113.79° and experimentally as 112.8°. These reported parameters have been similar to the optimized structure of gemcitabine and docetaxel complex, that confirms that the structural features of GEDT were in the reported range [43].…”
Section: Resultssupporting
confidence: 83%
“…It has been found that the enzymes Poly-ADP-ribose polymerase 1 (PARP-1) and PARP-2, which are more active during the cell cycle's S phase and have larger functions in DNA repair than previously believed, play a role in DNA repair and are known as DNA damage sensors. PARP inhibitors are involved in a semi-targeted therapy for ovarian and breast cancers linked to BRCA1 and BRCA2 [14,15]. By serving as a convergent vehicle for protein interaction, BRCA1 is thought to mediate the function of these proteins in DNA repair, transcriptional transactivation, and cell cycle control [16].…”
mentioning
confidence: 99%
“…Zhang et al also used hollow silica particles to deliver drugs to enhance therapeutic efficacy. Other applications of hollow silica nanoparticles in drug releasing, such as gated hybrid materials, , biocompatibility , and so forth, are not shown here. The details can be found in the review literature …”
Section: Introductionmentioning
confidence: 94%
“…Based on docking studies, guanidine-Cur complex clearly targets tumorsuppressing proteins in MCF-7 cells through hydrogen bonding and electrostatic interactions with lower binding affinity, leading to apoptosis. 131 Recently, the antimicrobial effects of Cur-loaded MSNs were evaluated against clinically isolated Porphyromonas gingivalis, which is the main cause of periodontal disease. According to the ndings, P. gingivalis was sensitive to the Cur-loaded MSNs at concentrations of 50-6.25 mg mL −1 with the greatest inhibition zone (p # 0.05) at the concentration of 50 mg mL −1 .…”
Section: Biological Activity Of Cur-loaded Msnsmentioning
confidence: 99%